Evaluation of human T-cell leukemia virus in vitro diagnostics using plasma specimens collected in Japan - Kusagawa, Shigeru; Kawana-Tachikawa, Ai; Matsubayashi, Keiji; Sobata, Rieko; Hamaguchi, Isao (BMC infectious diseases, 2023)
In vitro diagnostics (IVDs) for primary detection test/screening of human T-cell leukemia virus (HTLV) have recently been updated to new-generation products in Japan. In this study, the performance of these products was evaluated and discussed in terms of the usability of HTLV diagnosis in Japan. The performance of 10 HTLV IVDs for primary detection test and confirmatory/discriminatory test was evaluated. Plasma specimens that had been declared ineligible for transfusion were provided by the Japanese Red Cross Blood Center. The diagnostic specificity of the IVDs was 100% (160/160). Six sandwich assays resulted in all HTLV-1/HTLV-positive specimens being positive (46/46). On the other hand, one sandwich assay, IVD under development 2 (UD2), resulted in one HTLV-1-positive and one HTLV-positive specimen being negative (44/46, 95.7%). One indirect assay, HISCL HTLV-1, could not detect one HTLV-positive specimen (45/46, 97.8%), but the updated product, UD1, correctly detected it (46/46, 100%). Serodia HTLV-I, based on a particle agglutination assay, resulted in 44 of the 46 positive specimens, but could not detect two specimens (44/46, 95.7%). ESPLINE HTLV-I/II, based on an immunochromatography assay (ICA), was able to diagnose all specimens as positive (46/46, 100%). Six sandwich assays and an ICA demonstrated high diagnostic sensitivity and specificity and are recommended for use in HTLV diagnosis in conjunction with confirmatory/discriminatory test using the INNO-LIA HTLV-I/II Score.